The Effect of Palestinian Banking Credit Facilities on the Palestinian Economy - Sweis, Khalid Mohammad Hasan (International Journal of Economics and Financial Issues, 2017)
This study aimed at investigating the effect of credit facilities on the Palestinian economy. Several tests and statistical packages (e.g. the SPSS, frequencies, percentages and averages, means, One-way Analysis of Variance, and Cronbach's alpha) had been conducted and utilized to extract the reliability coefficient. The researcher distributed (79) questionnaires to workers serving in the Facility Departments in Palestinian banks; only (67) were collected and analyzed. The study showed that banks employ promising laws related to granting facilities; it also found that these banks have flexible facilities that play a significant role in achieving bank economic growth/development which, by its turn, affects national economy. The study also reveled that it is difficult, in some cases, to count on the economic feasibility presented by customers. The researcher suggested that fines should be given to the institutes that issue abnormal economic feasibilities for the sake of getting credit facilities from banks. The study also recommended that additional powers should be given to branch managers, and that customers' awareness of the importance of bank requests to monitor bank accounts should be stressed. Keywords: Effect of Credit, Banks Facilities, credit policies, Palestinian Economy JEL Classifications: E51, G21